1998
DOI: 10.2337/diabetes.47.11.1748
|View full text |Cite
|
Sign up to set email alerts
|

Role of hyperglucagonemia in catabolism associated with type 1 diabetes: effects on leucine metabolism and the resting metabolic rate.

Abstract: The catabolic state of poorly controlled type 1 diabetes has largely been attributed to insulin deficiency. However, the role of hyperglucagonemia, which occurs concomitantly with insulin deficiency, has not been fully investigated. We studied the effects of hyperglucagonemia during insulin deprivation on energy expenditure (using indirect calorimetry) and protein metabolism (using L-[1-(13)C,15N]leucine and L-[1-(13)C]leucine as tracers) in 12 type 1 diabetic subjects. Five protocols were used: insulin treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
42
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 41 publications
9
42
1
1
Order By: Relevance
“…The finding of increased oxygen consumption during insulin deprivation in type 1 diabetes is consistent with previous findings (14,15). The current study demonstrated that increased O 2 consumption at the whole-body level was associated with a decrease in MAPR.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The finding of increased oxygen consumption during insulin deprivation in type 1 diabetes is consistent with previous findings (14,15). The current study demonstrated that increased O 2 consumption at the whole-body level was associated with a decrease in MAPR.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, inhibition of glucagon secretion by somatostatin during insulin deprivation in type 1 diabetes reverses the increased O 2 consumption. Re-introduction of glucagon increased O 2 consumption in those subjects, demonstrating that high glucagon levels contributed to increased O 2 consumption during insulin deprivation (15). Glucagon has also been shown to increase O 2 consumption during insulin deficiency in nondiabetic healthy people (26).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This observation was confirmed in different studies showing that insulin deprivation in T1D results in increased oxygen consumption, suggesting increased rate of oxidative phosphorylation. 32,33 The recent immunohistochemical analysis of a pancreatic gland from a patient with longstanding diabetes provided interesting clues to disease pathogenesis. 4 Interestingly, the remaining b-cells were detected in islets and within the exocrine pancreas in close vicinity of T-lymphocytes or macrophages This is consistent with the existence of a persistent autoimmune process and the inability of b-cells to regenerate from ductal cell precursors.…”
Section: Discussionmentioning
confidence: 99%